EKPLORASI PERAN FORUM KESEHATAN DESA (FKD) DALAM PEROLEHAN STRATA DESA SIAGA DI KABUPATEN BLORA - Durotun Maqfirah; Syamsulhuda BM; Priyadi Nugraha Prabamurti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Background : Desa Siaga program is useful to improve the community's health status independently, specifically reducing mortality, morbidity and nutritional status. In 2016, Blora Regency was ranked 5th with the highest mortality rate. The number of villages that have independent strata is still very small, coupled with a decrease in strata in various villages.Purpose : to analyze the Role of the Village Health Forum (FKD) in obtaining strata of Desa Siaga in Blora Regency.Method : Type of qualitative research with a descriptive approach. Data collection is done through in-depth interviews and observations. The main informants were 21 people consisting of village midwives and administrators of the Village Health Forum (FKD).Results : showed an increase in the Desa Siaga strata due to: a) Addition to the activity section, b) Management reorganization, c) Routine running meetings, d) The role of the puskesmas, e) Funds for independent community, community and private businesses, f) Having their own building, g) Systematic planning, h) Active forum, i) Support from the community and village government. While the decrease in the Desa Siaga strata was due to: a) The Management did not know the main tasks and functions of the Village Health Forum (FKD), b) There was no management reorganization, c) The village was still dependent on the Community Health Centers, d) There was no guidance for the village who could not afford fostered, e) Only have one source of funds, f) Non-systematic planning, g) Activities outside the forum, h) Lack of coordination, and i) The village head is not aware of the existence of the Village Health Forum in his village.Advice : given are: a) Empowering the village apparatus to be administrators, b) Organizing reorganization, c) Carrying out regular meetings, d) Raising independent funds from the community, e) Seeking financial support and infrastructure for business owners, f) Conducting systematic planning and g) seeking sustainable support from the community and village government.